An irradiation resistant titanium-silver alloy and a method of making the same
Patent Information
- Application Number
- CN202610939898.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-26
- Publication Date
- 2026-10-09
AI Technical Summary
现有抗辐照钛银合金多采用常规熔炼制备,易引入坩埚杂质,杂质在辐照下成为有害缺陷形核核心,加速性能劣化;Ag元素分布不均,无法形成连续的辐照缺陷捕获网络,抗辐照效率低;均匀成分合金易出现局部应力集中,高温抗蠕变性能不足,且服役过程中He原子易聚集形成气泡,导致材料提前开裂
本发明将工业纯钛为基体、纳米银粉为功能添加剂,通过真空电磁悬浮熔炼、电化学梯度扩散、分级时效热处理及低剂量He+预注入四步协同,以实现优异抗辐照性能与力学性能的效果。
Smart Images

Figure SMS_21
Abstract
Description
Technical Field
[0001] This invention relates to the field of titanium-silver alloy technology, specifically to a radiation-resistant titanium-silver alloy and its preparation method. Background Technology
[0002] Titanium alloys, due to their high temperature resistance and corrosion resistance, are key structural materials in nuclear reactors and aerospace irradiation environments. However, ordinary titanium alloys are prone to defects such as vacancies and dislocation loops under high-dose irradiation, leading to material swelling, embrittlement, and performance failure. Existing radiation-resistant titanium-silver alloys are mostly prepared using conventional melting, which easily introduces crucible impurities. These impurities become nucleation sites for harmful defects under irradiation, accelerating performance degradation. Uneven Ag distribution prevents the formation of a continuous irradiation defect trapping network, resulting in low radiation resistance efficiency. Homogeneous alloys are prone to localized stress concentration, insufficient high-temperature creep resistance, and He atoms tend to aggregate and form bubbles during service, leading to premature cracking. Existing processes cannot simultaneously achieve high-purity homogeneous preparation, three-dimensional defect trap construction, stress relief, and He aggregation suppression, failing to meet the core requirements for long-life service of titanium-silver alloys under irradiation environments. Summary of the Invention
[0003] The purpose of this invention is to provide a radiation-resistant titanium-silver alloy and its preparation method, so as to solve the problems existing in the prior art.
[0004] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for preparing a radiation-resistant titanium-silver alloy, comprising the following steps: (1) Weigh industrial pure titanium and high-purity nano silver powder at a mass ratio of 92~99:1~8, and spread the material using a layered alternating loading method. Perform vacuum electromagnetic levitation melting treatment, evacuate the vacuum, introduce high-purity argon gas, gradually increase the power to 20~50kW, maintain the molten state for 5~10min, and use electromagnetic force to fully stir and homogenize the melt. Cut off the power supply, and the melt solidifies rapidly in the suspended state. After the furnace cools to room temperature, take out the ingot; (2) Cut the ingot wire into block samples, pre-treat them, and then perform electrochemical gradient activation. Add electrolyte, use the block sample as the anode, the platinum sheet as the counter electrode, and the saturated calomel electrode as the reference. First stage: constant current 0.5mA / cm², 10min; Second stage: step voltage increase 30V→60V→100V, each voltage segment is maintained for 1~2h, and the total treatment time is 3~6h. Take out the sample after electrochemical gradient activation treatment, wash and dry it with deionized water, and perform graded aging heat treatment. First, heat up to 400℃ and simultaneously introduce high-purity argon gas and keep it at the temperature for 2h; then heat up to 550℃ and keep it at the temperature for 4h; after aging, cool it with the furnace to below 400℃ and take it out to air cool to room temperature. (3) The alloy samples that have undergone graded aging heat treatment are ground and polished to a mirror finish step by step, followed by ultrasonic cleaning for 15 minutes and drying with nitrogen. Irradiation preconditioning is performed using... Ion beam treatment, with controlled flux, was performed under vacuum at room temperature. After treatment, vacuum was continued for 10-15 minutes, followed by slow introduction of high-purity nitrogen to atmospheric pressure. The sample was then removed and its surface was gently wiped to obtain a radiation-resistant titanium-silver alloy.
[0005] Furthermore, the high-purity nano-silver powder mentioned in step (1) is: high-purity nano-silver powder with a particle size of 6nm.
[0006] Furthermore, the layered alternating loading method described in step (1) is as follows: the titanium material is laid at the bottom, a layer of silver powder is sprinkled, and then the titanium material is covered again, and this process is repeated until the crucible is full.
[0007] Furthermore, the block sample in step (2) is a block sample of 10mm×10mm×5mm.
[0008] Further, the pretreatment in step (2) is as follows: the surface is polished with 240#→600#→1000#→2000# SiC sandpaper until Ra≤0.8μm, ultrasonically cleaned with acetone and anhydrous ethanol for 15min each, and dried with cold air.
[0009] Furthermore, the electrolyte in step (2) is: 0.3 wt.% NH4F + 2 vol.% deionized water + 1.5 mol / L lactic acid, and the solvent is ethylene glycol.
[0010] Furthermore, the heating rate in step (2) is 5℃ / min.
[0011] Furthermore, the gas flow rate in step (2) is 0.5 L / min.
[0012] Furthermore, step (3) described The ion beam has an energy of 80~120 keV. Ion beam.
[0013] Furthermore, step (3) described The ion beam flux is: .
[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: This invention uses industrial pure titanium as the matrix and nano-silver powder as the functional additive, and employs vacuum electromagnetic levitation melting, electrochemical gradient diffusion, staged aging heat treatment, and low-dose He... + The four-step pre-injection process works synergistically to achieve excellent radiation resistance and mechanical properties.
[0015] This invention first uses industrial pure titanium as the matrix and nano-silver powder as the functional additive, and then employs vacuum electromagnetic levitation melting, electrochemical gradient diffusion, staged aging heat treatment, and low-dose He... +A four-step pre-injection process synergistically forms a three-dimensional nano-precipitation network along grain boundaries, characterized by silver-rich / titanium-poor deposits, resulting in a radiation-resistant titanium-silver alloy. Vacuum electromagnetic levitation melting, through electromagnetic stirring, ensures uniform Ag distribution within the titanium matrix. Simultaneously, the electromagnetic levitation state prevents crucible contamination, yielding a high-purity, homogeneous Ti-Ag ingot. This high purity prevents impurities from becoming nucleation sites for harmful defects under irradiation, thus preventing premature performance degradation. The high homogeneity provides a compositional benchmark for subsequent electrochemical treatment. Electrochemical gradient diffusion treatment allows for the formation of F... - Preferential activation under a stepped electric field leads to deep coupling between the Ag diffusion network and the grain boundaries within the material, forming a three-dimensional nano-Ag defect trap network. This endows the material with excellent radiation resistance. Simultaneously, the introduction of a compositional gradient distribution in the alloy eliminates localized stress concentrations that may occur in traditional homogeneous alloys, further enhancing the material's mechanical properties. Graded aging heat treatment allows the nano-sized Ag precipitates to act as second-phase particles, creating a strong pinning effect on grain boundaries and dislocation movement, improving high-temperature creep resistance while also trapping radiation defects to enhance radiation resistance. Pre-implanted He... + The formation of a stable He-V complex with vacancies avoids the violent aggregation of He atoms under high-dose irradiation during service, thus extending the service life of the material. At the same time, the early segregation of Ag makes the nanonetwork more complete, further improving the radiation resistance. Detailed Implementation
[0016] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0017] To more clearly illustrate the method provided by the present invention, the following embodiments are provided in detail. The testing methods for various properties of the titanium-silver alloy produced in the following embodiments are as follows: Compressive strength test: The alloy materials prepared in Examples 1-5 and Comparative Examples 1-5 were tested according to GB / T 7314-2017 "Metallic Materials - Room Temperature Compression Test Method".
[0018] Radiation resistance test: Using an X-ray machine as the radiation source, the alloy materials prepared in Examples 1-5 and Comparative Examples 1-5 were placed under a radiation energy of 2J for 30 minutes. The radiation dose meter readings during the radiation period were measured on the back of the alloy materials using a SIM-MAX G3160 radiation dose meter. Example 1
[0019] (1) Weigh industrial pure titanium and high-purity nano-silver powder with a particle size of 6 nm at a mass ratio of 92:8. Use a layered alternating loading method: place the titanium material at the bottom, sprinkle a layer of silver powder, and then cover it with titanium material. Repeat until the crucible is full. This can avoid excessive splashing of silver powder in the electromagnetic field. Perform vacuum electromagnetic levitation melting. Place the crucible with the materials in the center of the induction coil and evacuate to ≤5×10 - 3 Pa. Introduce high-purity argon gas to 0.5 atm, gradually increase the power to 20 kW, and observe the material turning red → melting → forming suspended droplets or a complete molten pool. Maintain the molten state for 5 minutes, and use electromagnetic force to fully stir and homogenize the melt. Cut off the power, and the melt will solidify rapidly in a suspended state. After the furnace cools to room temperature, remove the ingot. (2) Cut the ingot wire into 10mm×10mm×5mm block samples. Polish the surface with 240#→600#→1000#→2000# SiC sandpaper until Ra≤0.8μm. Clean the sample with acetone and anhydrous ethanol for 15min each. Dry it with cold air and perform electrochemical gradient activation. The electrolyte is 0.3wt.% NH4F+2vol.% deionized water+1.5mol / L lactic acid and the solvent is ethylene glycol. The block sample is the anode, the platinum sheet is the counter electrode, and the saturated calomel electrode is the reference. The first stage is constant current of 0.5mA / cm² for 10min to form the initial oxide film. The second stage is stepped voltage increase of 30V→60V→100V, each voltage segment is maintained for 1h, and the total treatment time is 3h. Take out the sample after electrochemical gradient activation treatment, wash it with deionized water and dry it. (3) The sample that has undergone electrochemical gradient activation treatment is subjected to graded aging heat treatment. The first low-temperature aging treatment parameters are: heating to 400℃ at 5℃ / min, while introducing high-purity argon gas at 0.5L / min, and holding for 2h to induce the precipitation of the ω phase transition phase, providing uniform nucleation sites for the subsequent α phase and Ag-enriched precipitates; the subsequent high-temperature treatment parameters are: heating to 550℃ at 5℃ / min, and holding for 4h, where Ag elements are enriched and precipitated along grain boundaries and phase boundaries to form nanoscale Ag precipitates, which have a pinning effect on grain boundaries; after aging, the sample is cooled to below 400℃ in the furnace and then air-cooled to room temperature. (4) The alloy samples that have undergone graded aging heat treatment are ground step by step to 2000# sandpaper and polished to a mirror finish with diamond polishing paste. Then, they are ultrasonically cleaned for 15 minutes each in deionized water, acetone, and anhydrous ethanol to remove surface contaminants. After drying with nitrogen, they are ready for use. Irradiation preconditioning uses an energy of 80 keV. Ion beam, flux controlled at Between, irradiation at room temperature and vacuum The process was carried out under the following conditions. After the treatment was completed, the vacuum was continued for 10 minutes, and then high-purity nitrogen was slowly introduced to atmospheric pressure. The sample was then removed and the surface was gently wiped with a clean, soft cloth to obtain the radiation-resistant titanium-silver alloy. Example 2
[0020] (1) Weigh industrial pure titanium and high-purity nano-silver powder with a particle size of 6 nm at a mass ratio of 94:6. Use a layered alternating loading method: place the titanium material at the bottom, sprinkle a layer of silver powder, and then cover it with titanium material. Repeat until the crucible is full. This can avoid excessive splashing of silver powder in the electromagnetic field. Perform vacuum electromagnetic levitation melting. Place the crucible with the materials in the center of the induction coil and evacuate to ≤5×10 - 3 Pa. Introduce high-purity argon gas to 0.5 atm, gradually increase the power to 35 kW, and observe the material turning red → melting → forming suspended droplets or a complete molten pool. Maintain the molten state for 6 minutes, and use electromagnetic force to fully stir and homogenize the melt. Cut off the power, and the melt will solidify rapidly in a suspended state. After the furnace cools to room temperature, remove the ingot. (2) Cut the ingot wire into 10mm×10mm×5mm block samples. Polish the surface with 240#→600#→1000#→2000# SiC sandpaper until Ra≤0.8μm. Clean the sample with acetone and anhydrous ethanol for 15min each. Dry it with cold air and perform electrochemical gradient activation. The electrolyte is 0.3wt.% NH4F+2vol.% deionized water+1.5mol / L lactic acid and the solvent is ethylene glycol. The block sample is the anode, the platinum sheet is the counter electrode, and the saturated calomel electrode is the reference. Stage 1: constant current 0.5mA / cm², 10min, to form the initial oxide film. Stage 2: step voltage increase 30V→60V→100V, each voltage segment is maintained for 1.2h, and the total treatment time is 3.5h. Take out the sample treated with electrochemical gradient activation, wash it with deionized water and dry it. (3) The sample that has undergone electrochemical gradient activation treatment is subjected to graded aging heat treatment. The first low-temperature aging treatment parameters are: heating to 400℃ at 5℃ / min, while introducing high-purity argon gas at 0.5L / min, and holding for 2h to induce the precipitation of the ω phase transition phase, providing uniform nucleation sites for the subsequent α phase and Ag-enriched precipitates; the subsequent high-temperature treatment parameters are: heating to 550℃ at 5℃ / min, and holding for 4h, where Ag elements are enriched and precipitated along grain boundaries and phase boundaries to form nanoscale Ag precipitates, which have a pinning effect on grain boundaries; after aging, the sample is cooled to below 400℃ in the furnace and then air-cooled to room temperature. (4) The alloy samples that have undergone graded aging heat treatment are ground stepwise to 2000# sandpaper and polished to a mirror finish with diamond polishing paste. They are then ultrasonically cleaned for 15 minutes each in deionized water, acetone, and anhydrous ethanol to remove surface contaminants. After drying with nitrogen, they are ready for use. Irradiation preconditioning uses an energy of 90 keV. Ion beam, flux controlled at Between, irradiation at room temperature and vacuum The process was carried out under the following conditions. After the treatment was completed, the vacuum was continued for 12 minutes, and then high-purity nitrogen was slowly introduced to atmospheric pressure. The sample was then removed and the surface was gently wiped with a clean, soft cloth to obtain the radiation-resistant titanium-silver alloy. Example 3
[0021] (1) Weigh industrial pure titanium and high-purity nano-silver powder with a particle size of 6 nm at a mass ratio of 95:5. Use a layered alternating loading method: place the titanium material at the bottom, sprinkle a layer of silver powder, and then cover it with titanium material. Repeat until the crucible is full. This can avoid excessive splashing of silver powder in the electromagnetic field. Perform vacuum electromagnetic levitation melting. Place the crucible with the materials in the center of the induction coil and evacuate to ≤5×10. - 3 Pa. Introduce high-purity argon gas to 0.5 atm, gradually increase the power to 35 kW, and observe the material turning red → melting → forming suspended droplets or a complete molten pool. Maintain the molten state for 8 minutes, and use electromagnetic force to fully stir and homogenize the melt. Cut off the power, and the melt will solidify rapidly in a suspended state. After the furnace cools to room temperature, remove the ingot. (2) Cut the ingot wire into 10mm×10mm×5mm block samples. Polish the surface with 240#→600#→1000#→2000# SiC sandpaper until Ra≤0.8μm. Clean the sample with acetone and anhydrous ethanol for 15min each. Dry it with cold air and perform electrochemical gradient activation. The electrolyte is 0.3wt.% NH4F+2vol.% deionized water+1.5mol / L lactic acid and the solvent is ethylene glycol. The block sample is the anode, the platinum sheet is the counter electrode, and the saturated calomel electrode is the reference. The first stage is constant current of 0.5mA / cm² for 10min to form the initial oxide film. The second stage is stepped voltage increase of 30V→60V→100V, each voltage segment is maintained for 1.5h, and the total treatment time is 4.5h. Take out the sample after electrochemical gradient activation treatment, wash it with deionized water and dry it. (3) The sample that has undergone electrochemical gradient activation treatment is subjected to graded aging heat treatment. The first low-temperature aging treatment parameters are: heating to 400℃ at 5℃ / min, while introducing high-purity argon gas at 0.5L / min, and holding for 2h to induce the precipitation of the ω phase transition phase, providing uniform nucleation sites for the subsequent α phase and Ag-enriched precipitates; the subsequent high-temperature treatment parameters are: heating to 550℃ at 5℃ / min, and holding for 4h, where Ag elements are enriched and precipitated along grain boundaries and phase boundaries to form nanoscale Ag precipitates, which have a pinning effect on grain boundaries; after aging, the sample is cooled to below 400℃ in the furnace and then air-cooled to room temperature. (4) The alloy samples that have undergone graded aging heat treatment are ground stepwise to 2000# sandpaper and polished to a mirror finish with diamond polishing paste. They are then ultrasonically cleaned for 15 minutes each in deionized water, acetone, and anhydrous ethanol to remove surface contaminants. After drying with nitrogen, they are ready for use. Irradiation preconditioning uses an energy of 100 keV. Ion beam, flux controlled at Between, irradiation at room temperature and vacuum The process was carried out under the following conditions. After the treatment was completed, the vacuum was continued for 13 minutes, and then high-purity nitrogen was slowly introduced to atmospheric pressure. The sample was then removed and the surface was gently wiped with a clean, soft cloth to obtain the radiation-resistant titanium-silver alloy. Example 4
[0022] (1) Weigh industrial pure titanium and high-purity nano-silver powder with a particle size of 6 nm at a mass ratio of 97:3. Use a layered alternating loading method: place the titanium material at the bottom, sprinkle a layer of silver powder, and then cover it with titanium material. Repeat until the crucible is full. This can avoid excessive splashing of silver powder in the electromagnetic field. Perform vacuum electromagnetic levitation melting. Place the crucible with the materials in the center of the induction coil and evacuate to ≤5×10 - 3 Pa. Introduce high-purity argon gas to 0.5 atm, gradually increase the power to 45 kW, and observe the material turning red → melting → forming suspended droplets or a complete molten pool. Maintain the molten state for 9 minutes, and use electromagnetic force to fully stir and homogenize the melt. Cut off the power, and the melt will solidify rapidly in a suspended state. After the furnace cools to room temperature, remove the ingot. (2) Cut the ingot wire into 10mm×10mm×5mm block samples. Polish the surface with 240#→600#→1000#→2000# SiC sandpaper until Ra≤0.8μm. Clean the sample with acetone and anhydrous ethanol for 15min each. Dry it with cold air and perform electrochemical gradient activation. The electrolyte is 0.3wt.% NH4F+2vol.% deionized water+1.5mol / L lactic acid and the solvent is ethylene glycol. The block sample is the anode, the platinum sheet is the counter electrode, and the saturated calomel electrode is the reference. The first stage is constant current of 0.5mA / cm² for 10min to form the initial oxide film. The second stage is stepped voltage increase of 30V→60V→100V, each voltage segment is maintained for 1.8h, and the total treatment time is 5h. Take out the sample treated with electrochemical gradient activation, wash it with deionized water and dry it. (3) The sample that has undergone electrochemical gradient activation treatment is subjected to graded aging heat treatment. The first low-temperature aging treatment parameters are: heating to 400℃ at 5℃ / min, while introducing high-purity argon gas at 0.5L / min, and holding for 2h to induce the precipitation of the ω phase transition phase, providing uniform nucleation sites for the subsequent α phase and Ag-enriched precipitates; the subsequent high-temperature treatment parameters are: heating to 550℃ at 5℃ / min, and holding for 4h, where Ag elements are enriched and precipitated along grain boundaries and phase boundaries to form nanoscale Ag precipitates, which have a pinning effect on grain boundaries; after aging, the sample is cooled to below 400℃ in the furnace and then air-cooled to room temperature. (4) The alloy samples that have undergone graded aging heat treatment are ground stepwise to 2000# sandpaper and polished to a mirror finish with diamond polishing paste. They are then ultrasonically cleaned for 15 minutes each in deionized water, acetone, and anhydrous ethanol to remove surface contaminants. After drying with nitrogen, they are ready for use. Irradiation preconditioning uses an energy of 110 keV. Ion beam, with flux controlled within During this period, irradiation was carried out at room temperature and vacuum level. The process was carried out under the following conditions. After the treatment was completed, the vacuum was continued for 14 minutes, and then high-purity nitrogen was slowly introduced to atmospheric pressure. The sample was then removed and the surface was gently wiped with a clean, soft cloth to obtain the radiation-resistant titanium-silver alloy. Example 5
[0023] (1) Weigh industrial pure titanium and high-purity nano-silver powder with a particle size of 6 nm at a mass ratio of 99:1. Use a layered alternating loading method: place the titanium material at the bottom, sprinkle a layer of silver powder, and then cover it with titanium material. Repeat until the crucible is full. This can avoid excessive splashing of silver powder in the electromagnetic field. Perform vacuum electromagnetic levitation melting. Place the crucible with the material in the center of the induction coil and evacuate to ≤5×10 - 3 Pa. Introduce high-purity argon gas to 0.5 atm, gradually increase the power to 50 kW, and observe the material turning red → melting → forming suspended droplets or a complete molten pool. Maintain the molten state for 10 minutes, and use electromagnetic force to fully stir and homogenize the melt. Cut off the power, and the melt will solidify rapidly in a suspended state. After the furnace cools to room temperature, remove the ingot. (2) Cut the ingot wire into 10mm×10mm×5mm block samples. Polish the surface with 240#→600#→1000#→2000# SiC sandpaper until Ra≤0.8μm. Clean the sample with acetone and anhydrous ethanol for 15min each. Dry it with cold air and perform electrochemical gradient activation. The electrolyte is 0.3wt.% NH4F+2vol.% deionized water+1.5mol / L lactic acid and the solvent is ethylene glycol. The block sample is the anode, the platinum sheet is the counter electrode, and the saturated calomel electrode is the reference. Stage 1: constant current 0.5mA / cm², 10min, to form the initial oxide film. Stage 2: step voltage increase 30V→60V→100V, each voltage segment is maintained for 2h, and the total treatment time is 6h. Take out the sample treated with electrochemical gradient activation, wash it with deionized water and dry it. (3) The sample that has undergone electrochemical gradient activation treatment is subjected to graded aging heat treatment. The first low-temperature aging treatment parameters are: heating to 400℃ at 5℃ / min, while introducing high-purity argon gas at 0.5L / min, and holding for 2h to induce the precipitation of the ω phase transition phase, providing uniform nucleation sites for the subsequent α phase and Ag-enriched precipitates; the subsequent high-temperature treatment parameters are: heating to 550℃ at 5℃ / min, and holding for 4h, where Ag elements are enriched and precipitated along grain boundaries and phase boundaries to form nanoscale Ag precipitates, which have a pinning effect on grain boundaries; after aging, the sample is cooled to below 400℃ in the furnace and then air-cooled to room temperature. (4) The alloy samples that have undergone graded aging heat treatment are ground step by step to 2000# sandpaper and polished to a mirror finish with diamond polishing paste. Then, they are ultrasonically cleaned for 15 minutes each in deionized water, acetone, and anhydrous ethanol to remove surface contaminants. After drying with nitrogen, they are ready for use. Irradiation preconditioning uses 80~120keV energy. Ion beam, flux controlled at Between, irradiation at room temperature and vacuum The process was carried out under the following conditions. After the treatment was completed, the vacuum was continued for 15 minutes, and then high-purity nitrogen was slowly introduced to atmospheric pressure. The sample was then removed and the surface was gently wiped with a clean, soft cloth to obtain the radiation-resistant titanium-silver alloy.
[0024] Comparative Example 1 The difference between Comparative Example 1 and Example 3 is that only vacuum electromagnetic levitation melting treatment is performed, without electrochemical gradient treatment or graded aging.
[0025] Comparative Example 2 The difference between Comparative Example 2 and Example 3 is that the vacuum electromagnetic levitation melting process is not performed, while the other steps are the same as in Example 3.
[0026] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that no electrochemical gradient treatment was performed, while the remaining steps were the same as in Example 3.
[0027] Comparative Example 4 The difference between Comparative Example 4 and Example 3 is that no graded aging treatment is performed, while the remaining steps are the same as in Example 3.
[0028] Comparative Example 5 The difference between Comparative Example 5 and Example 3 is that low-dose He was not performed. + Pre-injection, the remaining steps are the same as in Example 3.
[0029] Example of effect Table 1 below shows the performance analysis results of the titanium-silver alloys of Examples 1 to 5 and Comparative Examples 1 to 5 of the present invention.
[0030]
[0031] A comparison of the compressive strength experimental data of the embodiments and comparative examples reveals that the present invention introduces a compositional gradient distribution into the alloy, eliminating local stress concentrations that may occur in traditional homogeneous alloys, thus further improving the mechanical properties of the material. A comparison of the radiation dose experimental data of the embodiments and comparative examples reveals that the vacuum electromagnetic levitation melting in the present invention achieves uniform Ag distribution in the titanium matrix through electromagnetic stirring. Simultaneously, the electromagnetic levitation state avoids crucible contamination, resulting in a high-purity, homogeneous Ti-Ag ingot. This high purity prevents impurity elements from becoming nucleation sites for harmful defects under irradiation, preventing premature performance degradation. The high homogeneity provides a compositional benchmark for subsequent electrochemical treatment. Electrochemical gradient diffusion treatment allows for the absorption of F... - Preferential activation under a stepped electric field leads to deep coupling between the Ag diffusion network and the grain boundaries within the material, forming a three-dimensional nano-Ag defect trap network, endowing the material with excellent radiation resistance. Graded aging heat treatment causes the nano-sized Ag precipitates to act as second-phase particles, creating a strong pinning effect on grain boundaries and dislocation movement, enhancing high-temperature creep resistance while also trapping radiation defects to further improve radiation resistance. Pre-implanted He... + The formation of a stable He-V complex with vacancies avoids the violent aggregation of He atoms under high-dose irradiation during service, thus extending the service life of the material. At the same time, the early segregation of Ag makes the nanonetwork more complete, further improving the radiation resistance.
[0032] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No markings in the claims should be construed as limiting the scope of the claims.
Claims
1. A method for preparing a radiation-resistant titanium-silver alloy, characterized in that, Includes the following steps: (1) Weigh industrial pure titanium and high-purity nano silver powder at a mass ratio of 92~99:1~8, and spread the material using a layered alternating loading method. Perform vacuum electromagnetic levitation melting treatment, evacuate the vacuum, introduce high-purity argon gas, gradually increase the power to 20~50kW, maintain the molten state for 5~10min, and use electromagnetic force to fully stir and homogenize the melt. Cut off the power supply, and the melt solidifies rapidly in the suspended state. After the furnace cools to room temperature, take out the ingot. (2) Cut the ingot wire into block samples, pre-treat them, and then perform electrochemical gradient activation. Add electrolyte, use the block sample as the anode, the platinum sheet as the counter electrode, and the saturated calomel electrode as the reference. First stage: constant current 0.5mA / cm², 10min; Second stage: step voltage increase 30V→60V→100V, each voltage segment is maintained for 1~2h, and the total treatment time is 3~6h. Take out the sample after electrochemical gradient activation treatment, wash and dry it with deionized water, and perform graded aging heat treatment. First, heat up to 400℃ and simultaneously introduce high-purity argon gas and keep it at the temperature for 2h; then heat up to 550℃ and keep it at the temperature for 4h; after aging, cool it with the furnace to below 400℃ and take it out to air cool to room temperature. (3) The alloy samples that have undergone graded aging heat treatment are ground and polished to a mirror finish step by step, followed by ultrasonic cleaning for 15 minutes and drying with nitrogen. Irradiation preconditioning is performed using... Ion beam treatment, with controlled flux, was performed under vacuum at room temperature. After treatment, vacuum was continued for 10-15 minutes, followed by slow introduction of high-purity nitrogen to atmospheric pressure. The sample was then removed and its surface was gently wiped to obtain a radiation-resistant titanium-silver alloy.
2. The radiation-resistant titanium-silver alloy according to claim 1, characterized in that, The high-purity nano-silver powder mentioned in step (1) is: high-purity nano-silver powder with a particle size of 6nm.
3. The radiation-resistant titanium-silver alloy according to claim 1, characterized in that, The layered alternating loading method described in step (1) is as follows: place titanium material at the bottom, sprinkle a layer of silver powder, cover with titanium material again, and repeat until the crucible is full.
4. The radiation-resistant titanium-silver alloy according to claim 1, characterized in that, The block sample in step (2) is a block sample of 10mm×10mm×5mm.
5. The radiation-resistant titanium-silver alloy according to claim 1, characterized in that, The pretreatment in step (2) is as follows: the surface is polished with 240#→600#→1000#→2000# SiC sandpaper until Ra≤0.8μm, ultrasonically cleaned with acetone and anhydrous ethanol for 15min each, and dried with cold air.
6. The radiation-resistant titanium-silver alloy according to claim 1, characterized in that, The electrolyte in step (2) is: 0.3 wt.% NH4F + 2 vol.% deionized water + 1.5 mol / L lactic acid, and the solvent is ethylene glycol.
7. The radiation-resistant titanium-silver alloy according to claim 1, characterized in that, The heating rate in step (2) is 5℃ / min.
8. The radiation-resistant titanium-silver alloy according to claim 1, characterized in that, The gas flow rate in step (2) is 0.5 L / min.
9. The radiation-resistant titanium-silver alloy according to claim 1, characterized in that, Step (3) The ion beam has an energy of 80~120 keV. Ion beam.
10. The radiation-resistant titanium-silver alloy according to claim 1, characterized in that, Step (3) The ion beam flux is: .